Ethnic minority entrepreneurship: Influencing factors of ethnic minority entrepreneurs’ entrepreneurial activities. - Sharif Hossain; Md Rubel Ahmed; Nurul Islam (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Ethnic minority entrepreneurs make a significant social and economic contribution with their entrepreneurial activities. This research, therefore, aims to clarify the meaning of ethnic minority entrepreneurship and highlight the factors that influence ethnic minority entrepreneurs’ decision to engage in entrepreneurial activities. Design/methodology/approach: In this secondary research, existing literature has been reviewed and integrated to highlight factors that influence ethnic minority entrepreneurs. Findings: This research could also create opportunities for further research in the ethnic minority entrepreneurship domain and help policymakers in understanding the needs of ethnic minority entrepreneurs. Research limitations/implications: These influencing factors are categorised into cultural aspects, disadvantage aspects, opportunity aspect and the resource aspect. Practical implications: Insight of this paper could help to clarify the meaning of ethnic minority entrepreneurship and provide a better understanding of the drivers and barriers of it. Originality/value: This paper is original Paper type: Research paper